Interleukin-6 Induces DEC1, Promotes DEC1 Interaction with RXRα and Suppresses the Expression of PXR, CAR and Their Target Genes - Ning, Rui; Zhan, Yunran; He, Shuangcheng; Hu, Jinhua; Zhu, Zhu; Hu, Gang; Yan, Bingfang; Yang, Jian; Liu, Wei (Frontiers in Pharmacology, 2017)
Inflammatory burden is a primary cellular event in many liver diseases, and the overall capacity of drug elimination is decreased. PXR (pregnane X receptor) and CAR (constitutive androstane receptor) are two master regulators of genes encoding drug-metabolizing enzymes and transporters. DEC1 (differentiated embryonic chondrocyte-expressed gene 1) is a ligand-independent transcription factor and reportedly is induced by many inflammatory cytokines including IL-6. In this study, we used primary hepatocytes (human and mouse) as well as HepG2 cell line and demonstrated that IL-6 increased DEC1 expression and decreased the expressions of PXR, CAR, and their target genes. Overexpression of DEC1 had similar effect as IL-6 on the expression of these genes, and knockdown of DEC1 reversed their downregulation by IL-6 . Interestingly, neither IL-6 nor DEC1 altered the expression of RXRα, a common dimerization partner for many nuclear receptors including PXR and CAR. Instead, DEC1 was found to interact with RXRα and IL-6 enhanced the interaction. These results conclude that DEC1 uses divese mechanisms of action and supports IL-6 downregulation of drug-elimination genes and their regulators.